The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/cas.13256
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor effect of focal adhesion kinase inhibitor PF562271 against human osteosarcoma in vitro and in vivo

Abstract: Focal adhesion kinase (FAK) overexpression is related to invasive and metastatic properties in different kinds of cancers. Target therapy by inhibiting FAK has achieved promising effect in some cancer treatments, but its effect in human osteosarcoma has not been well studied. In the present study, we analyzed the antitumor efficacy of PF562271, an FAK inhibitor, against osteosarcoma in vitro and in vivo. Phosphorylated FAK (Y397) was highly expressed in primary human osteosarcoma tumor samples and was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Focal adhesion is a key regulator of multi-cellular signaling pathways in cell proliferation, cycle regression, migration, apoptosis, and survival [33]. Hu et al [34] assessed the effects of the small-molecule focal adhesion inhibitor PF562271 on OS cells and showed that it diminished OS cell volume, weight, and angiogenesis and concluded that inhibition of focal adhesion could therefore be a target for OS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion is a key regulator of multi-cellular signaling pathways in cell proliferation, cycle regression, migration, apoptosis, and survival [33]. Hu et al [34] assessed the effects of the small-molecule focal adhesion inhibitor PF562271 on OS cells and showed that it diminished OS cell volume, weight, and angiogenesis and concluded that inhibition of focal adhesion could therefore be a target for OS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion expression has been suggested to be associated with cell migration and normally indicates a poor prognosis (36). Focal adhesion and the ECM have been commonly associated in osteosarcomas, with these factors investigated as potential antitumor targets (37,38). In the present study, 4 differentially expressed genes ( ALCAM, SDC1, CDH2 and HLA-DMA ) associated with the 9 lncRNAs in the risk assessment model were significantly involved in CAMs.…”
Section: Discussionmentioning
confidence: 99%
“…After a 14-day incubation, the media were aspirated from each well and the cells were stained with 1% crystal violet for 30 min. The number of colonies in each well was counted with plates tested in duplicate as described in a previous study 39 .…”
Section: Methodsmentioning
confidence: 99%